Między emocjami a estetyką słowa - o roli piękna języka w wypowiedziach dziennikarzy sportowych = Between emotions and aesthetics - on the role of language beauty in sports journalism - Grochala, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sports journalism is mostly based on the direct description of sports events and its accompanying emotions. Its expressiveness, alongside with the need to capture the readers` attention, quite often (if not usually) cause the texts to be of lower aesthetic value.
Keywords: dziennikarstwo sportowe; językowe środki wyrażania emocji; estetyka słowa; Tomaszewski, Bohdan (1921-2015); sports journalism; expressing emotions in the language; aesthetics